APPLICATION OF CORAL TRANSPLANTATION TECHNOLOGY FOR CORAL REEF ECOSYSTEM PROBLEMS IN SALAH NAMA ISLAND, BATUBARA REGENCY - Ipanna Enggar Susetya; Desrita; Zulham Apandy Harahap (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Coral reefs are one of the typical ecosystems in coastal areas that have ecological and economicvalue. There are many cases of coral reef damage in Salah Nama Island caused by natural andhuman factors. Coral reefs damage is mostly caused by human activities such as water pollution,destructive fishing and using of ship anchors. Activity of devotion society aims to provideinformation and skills to fishermen groups in Salah Nama Island about coral transplantationtechniques, as well as conducting coral transplantation activities as one of the efforts to preservethe ecosystem of coral reefs. Based on the description of the problems and objectives of devotionsociety, the activities that have been done are counseling to the partner fishermen abouttransplantation and coral benefits in ecosystem, transplantation practice and coral transplantationmonitoring.